Formulasi, Implementasi Undang-Undang Desa Nomor 6 Tahun 2014 Tentang Desa (Studi Kasus Desa Kota Bani Kecamatan Putri Hijau Kabupaten Bengkulu Utara). - Yohanes Susanto (STIA Bengkulu, 2023)
This study will discuss how the formulation and implementation of Village Law no. 6 of 2014 concerning Villages, which was held in Kota Bani Village, Putri Hijau District, North Bengkulu Regency. In this study using a qualitative descriptive method with data collection techniques through in-depth interviews and documents. The main focus of this research is the extent to which the formulation and implementation of Village Law no. 6 of 2014 concerning Villages, which was held in Kota Bani Village, Putri Hijau District, North Bengkulu Regency. Based on this research, the results of the study showed that the formulation and implementation of Village Law no. 6 of 2014 concerning Villages which was held in Kota Bani Village, Putri Hijau Subdistrict, North Bengkulu Regency has been running very well as evidenced by the inclusion of Kota Bani Village, Putri Hijau Subdistrict, North Bengkulu Regency, which was ranked 6th out of the 100 best villages in Indonesia. However, it is undeniable that this achievement is influenced by both supporting and inhibiting factors, where the supporting factors are influenced by good village government cooperation and good village fund budget management, and the inhibiting factors include the low community participation and the lazy culture of the community to be actively involved in advance the village.